Stepping stone or dead end? The effect of the EITC on earnings growth - Molly Dahl; Thomas DeLeire; Jonathan Schwabish (Institute for the Study of Labor (IZA), 2009)
While many studies have found that the EITC increases the employment rates of single mothers, no study to date has examined whether the jobs taken by single mothers as a result of the EITC incentives are dead-end jobs or jobs that have the potential for earnings growth. Using a panel of administrative earnings data linked to nationally representative survey data, we find no evidence that the EITC expansions between 1994 and 1996 induced single mothers to take dead-end jobs. If anything, the increase in earnings growth during the mid-to-late 1990s for single mothers who were particularly affected by the EITC expansion was higher than it was for other similar women. The EITC encourages work among single mothers, and that work continues to pay off through future increases in earnings.
urn:nbn:de:101:1-20090513444
Keywords: J3; H2; 330; Earned income tax credit; earnings; single mothers; Einkommensteuer; Steuerbegünstigung; Alleinerziehende; Frauenerwerbstätigkeit; Erwerbsverlauf; USA